The Effect of Capital Intensity, Thin Capitalization, and Environmental Disclosure on Tax Avoidance - Panjaitan, Aldenya Estlyen Mattea; Hisar Pangaribuan,; Mila Susanti, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study investigates whether capital intensity, thin capitalization, and environmental disclosure influence corporate tax avoidance in Indonesian listed financial sector firms during 2021 to 2024. Tax avoidance is proxied by the cash effective tax rate (CETR). Capital intensity is measured by the proportion of fixed assets, thin capitalization is proxied by the debt to equity ratio, and environmental disclosure is measured using an index based on GRI 300 indicators. Using purposive sampling, the study obtained 21 firms and applied multiple linear regression to firm year observations. The results indicate that thin capitalization has a significant negative effect on CETR, implying that higher leverage is associated with lower cash tax payments and a greater tendency toward tax avoidance. In contrast, capital intensity and environmental disclosure do not show statistically significant effects on CETR. The model explains a limited proportion of CETR variation, suggesting that tax avoidance in the financial sector is shaped by additional firm-specific and regulatory factors beyond the variables examined. The findings contribute sector-specific evidence on the determinants of tax avoidance in a highly regulated industry and provide implications for policymakers regarding the monitoring of leverage-related tax planning.